2008
DOI: 10.1016/j.chemosphere.2008.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in soils of three agricultural experimental stations with long-term fertilization in China

Abstract: a b s t r a c tMercury (Hg) in the agricultural ecosystem is a global concern because of its high potential toxicity. The objectives of this study were to determine the concentration and distribution of Hg in soils from three long-term experimental stations, i.e., Taoyuan (TY) and Qiyang (QY) in Hunan Province and Fengqiu (FQ) in Henan Province of China, and thus to assess the possible food and health risk of long-term applications of fertilizers. Soil samples at each site were collected from different fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…However, Li et al (2010) found that the variation of geological source but not exogenous factors played a more dominant role in determining As concentration in soil. However, the application of long-term fertilization increased organic carbon concentration (Liu et al 2013;Yang et al 2011) and the content of phosphorus (P) (Ge et al 2008;Zheng et al 2008a) and changed the acidity of soil depending on the soil conditions (Dong et al 2012;Zheng et al 2008b). Meanwhile, the release of metal including As from the solid phase of soil was influenced by organic carbon based on the formation of soluble metal-organic complexes (Cao et al 2003;Grafe et al 2002;Harvey et al 2002;Jackson et al 2006;Mladenov et al 2010;Wang and Mulligan 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, Li et al (2010) found that the variation of geological source but not exogenous factors played a more dominant role in determining As concentration in soil. However, the application of long-term fertilization increased organic carbon concentration (Liu et al 2013;Yang et al 2011) and the content of phosphorus (P) (Ge et al 2008;Zheng et al 2008a) and changed the acidity of soil depending on the soil conditions (Dong et al 2012;Zheng et al 2008b). Meanwhile, the release of metal including As from the solid phase of soil was influenced by organic carbon based on the formation of soluble metal-organic complexes (Cao et al 2003;Grafe et al 2002;Harvey et al 2002;Jackson et al 2006;Mladenov et al 2010;Wang and Mulligan 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This can affect the bioavailability of micro and macroelements, as well as heavy metals, and thus determine the plant nutrition and consequently the amount and quality of agricultural crops (Zimny et al 2005, Mainville et al 2006, Zheng et al 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition of pollutants from the atmosphere and agricultural activities, including the use of pesticides and fertilizers, can often lead to mercury accumulation in soil where the content of this element exceeds 2 mg/kg of fertilizer or adjuvant (Filipek 2003, Lu et al 2006, Kyllönen et al 2009). Literature shows that the mercury content after the long-term application of high dose of P and K fertilizers often increases, particularly in soils which are characterized by a low mercury geochemical background (Zheng et al 2008, Jaguś et al 2013. The mercury content in phosphate fertilizers is 0.01-1.20 mg/kg (Kabata-Pendias and Pendias 2001), and in calcium superphosphate may reach up to 5.1 mg/kg (Zhao and Wang 2010).…”
mentioning
confidence: 99%
“…However, knowledge of the effect of long-term fertilization on the merA gene diversity is particularly scarce. Previous study has reported the potential Hg pollution soil with long-term fertilization in the Qiyang experimental station, Hunan Province, China [25]. The Hg in this soil was mainly originated from soil parent materials but not an anthropogenic input.…”
mentioning
confidence: 98%